Morphometric analysis of the infraorbital groove, canal, and foramen on computed tomography scans of an Iranian population = Análisis morfométrico del surco, canal y foramen infraorbitario en tomografías computarizadas de una población iraní - Vaezi, Mojtaba
This study morphometrically assessed the infraorbital groove (IOG), canal (IOC) and foramen (IOF) on computed tomography (CT) scans of an Iranian population. This cross-sectional study evaluated the CT scans of 126 patients presenting to a hospital in Qazvin city, Iran during 2020-2022, who were selected by convenience sampling. An oral and maxillofacial surgeon and an oral and maxillofacial radiologist identified the relevant anatomical landmarks and the measurements were made by a trained senior dental student. Data were analyzed by independent t-test, and Pearson's correlation test (alpha=0.05). The mean IOC length was 9.86±1.34 mm, the mean IOG length was 12.78±1.57 mm, the mean IOC-IOG angle was 136.78±6.90 degrees, the mean IOC-vertical plane angle was 26.92±5.74 degrees, the mean IOC-horizontal plane angle was 58.54±6.18 degrees, the mean horizontal distance between the IOF and the sagittal plane passing through the supraorbital notch (SON) was 4.85±0.98 mm, the mean horizontal distance between the IOF and the sagittal plane passing through the midline was 23.04±2.90 mm, the mean vertical distance between the IOF and infraorbital rim (IOR) was 9.22±1.45 mm, the mean distance between the IOF and anterior nasal spine (ANS) was 27.63±10.99 mm, the mean angle between the IOF and ANS was 33.52±5.46 degrees, and the mean soft tissue thickness over the IOF was 10.60±2.04 mm. No significant difference was found in the parameters based on age (P>0.05). IOF-midline and IOF-IOR distances were significantly greater in males than females (P<0.05). No other significant differences were found based on gender (P>0.05). According to the results, the IOF-midline and IOF-IOR distances were significantly greater in Iranian males than females. The obtained results regarding the position of IOC, IOF, and IOG on CT scans of the Iranian study population can help maximize the success of related clinical procedures.